The power and the glorification: papal pretensions and the art of propaganda in the fifteenth and sixteenth centuries - Jong, Jan L. de (Pennsylvania State University Press, 2013)
"Studies the propagandistic and political features of five prominent series of frescoes originating in papal Rome in the fifteenth and sixteenth centuries. Discusses the manipulation of historical events for propagandistic purposes, the importance of inscriptions in controlling interpretation, and the reactions of contemporary viewers"--Provided by publisher